2020
DOI: 10.1021/acs.jpca.9b10705
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Benzyl Radicals: Kinetics and Spectroscopy in a Shock Tube

Abstract: Understanding the mechanism of high-temperature reactions of aromatic hydrocarbons and radicals is essential for the modeling of hydrocarbon growth processes in combustion environments. In this study, the thermal decomposition reaction of benzyl radicals was investigated using time-resolved broadband cavity-enhanced absorption spectroscopy behind reflected shock waves at a postshock pressure of 100 kPa and temperatures of 1530, 1630, and 1740 K. The transient absorption spectra during the decomposition were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 72 publications
1
10
0
Order By: Relevance
“…CNT nucleation is notably a function of hydrocarbon thermal decomposition to suitable fragments (C2 units). C2 formation from thermal decomposition of toluene [ 47 , 48 , 49 ] can occur via several pathways. For example, toluene can decompose either through benzyl radical (Equation (3)) or phenyl radical (Equation (4)) formation; however, the former dominates at the temperatures applied in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…CNT nucleation is notably a function of hydrocarbon thermal decomposition to suitable fragments (C2 units). C2 formation from thermal decomposition of toluene [ 47 , 48 , 49 ] can occur via several pathways. For example, toluene can decompose either through benzyl radical (Equation (3)) or phenyl radical (Equation (4)) formation; however, the former dominates at the temperatures applied in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…ortho -Benzyne has captivated chemists for over 90 years, thanks, in part, to the species having both aryne and biradical character, which in turn affects its reactivity. , Yet, its potential to form large aromatic structures in combustion reactions has only recently been recognized. , In fact, studies with o -benzyne are proving to be increasingly important to investigate, as more research emerges showing the formation of o -benzyne in both combustion and astrochemically relevant environments . Subsequently, reactions of RSRs with o -benzyne represent alternative pathways to polycyclic hydrocarbons.…”
mentioning
confidence: 99%
“…Overall, the reaction of ortho ‐benzyne with vinylacetylene is concluded to represent a viable source of naphthalene and naphthyl radicals providing that the concentration of o ‐C 6 H 4 in a particular flame is sufficient. For instance, ortho ‐benzyne was identified as a significant transient species in a shock‐tube study of thermal decomposition of benzyl radicals [3] meaning that [ o ‐C 6 H 4 ] could be relatively high in toluene flames. Theoretical calculations showed that the branching ratio of the o ‐C 6 H 4 +CH 3 channel in benzyl decomposition is close to 50 % at 1 bar [43] .…”
Section: Discussionmentioning
confidence: 99%
“…ortho ‐Benzyne, o ‐C 6 H 4 , being a molecule with both aryne and biradical character, has intrigued chemists for more than 90 years, because such a mixed character is reflected by its special reactivity [1,2] . In recent years, more experimental studies on the formation of o ‐benzyne in both combustion [3,4] and astrochemically relevant environments [5] emerge and there has been a continuing interest to a potential role that o ‐benzyne and its larger analogs – polycyclic aromatic alkynes, may play in the growth processes of polycyclic aromatic hydrocarbons (PAH). o ‐C 6 H 4 has been identified as the main thermodynamically favorable product of the thermal unimolecular decomposition of phenyl radical, C 6 H 5 , [6–10] where a C−H bond in the ortho position with respect to the radical site is relatively weak, 79.7 kcal/mol [11] .…”
Section: Introductionmentioning
confidence: 99%